2021
DOI: 10.21608/ejchem.2021.60640.3305
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Characterization and Anticancer Evaluation of Novel Mixed Complexes Derived from 2-(1H-Benzimizadol-2-yl)aniline Schiff base and 2-Mercaptobenzimidazole or 2-Aminobenzothiazole

Abstract: Two Schiff base ligands ((benzimidazol-2-phenyl)iminomethyl)phenol (HL1) (1) and 2-(1-H-benzimidazol-2yl)phenyl)imino)methyl) naphthol (HL2) (2) were synthesized via condensation of 2-(1H-benzimizadol-2-yl)aniline and respectively salicylaldehyde or naphtylaldehyde. The synthesis of mixed complexes (3)-(6) was realized by reacting ligands HL1 (1) and HL2 (2), copper salt (CuCl2.2H2O) and respectively one equivalent of 2-mercaptobenzothiazole or 2aminobenzothiazole. The ligands as well as the metal complexes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The discovery of new α-glucosidase and α-amylase inhibitor agents is an interesting method of obtaining such drugs. To contribute to the advancement of the design and the discovery of new bioactive species [ 66 , 67 , 68 , 69 , 70 , 71 ], we combined the two patterns, benzimidazole and urea, in the same molecule, allowing for potential antidiabetic agents, and having good anti-oxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of new α-glucosidase and α-amylase inhibitor agents is an interesting method of obtaining such drugs. To contribute to the advancement of the design and the discovery of new bioactive species [ 66 , 67 , 68 , 69 , 70 , 71 ], we combined the two patterns, benzimidazole and urea, in the same molecule, allowing for potential antidiabetic agents, and having good anti-oxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…7 The importance of benzothiazoles as ligands is increased through benzothiazole derivatives containing additional donor atoms, such as nitrogen, sulfur, or oxygen, that can coordinate bidentately through two nitrogen atoms 8,9 or nitrogen and oxygen atoms. 10 The different coordination methods adopted by benzothiazole derivatives result from the diversity of uses of the complexes of these derivatives in the biological field; benzothiazole derivatives and their complexes show different biological activities, such as antimicrobial activity, 11 antitumor activity, 12,13 inhibition of enzymes 14 and Alzheimer's disease, 15 and cytotoxic activity. 16 Metal complexes with heterocyclic ligands containing heteroatoms, such as nitrogen, sulfur, or oxygen, are of interest as simple structural models of more complex biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…17 Transition-metal ions also play a vital role in biological processes and can form complexes with benzothiazole derivatives that exhibit enhanced biological activity. Benzothiazoles with a benzoylamino moiety substituted at the 2 position have a variety of biological properties, including antitumor 18 and antibacterial 13 properties. Because the coordination chemistry of N-(1,3-benzothiazol-2-yl)benzamide (HL) has not been extensively studied, the aim of the current study was to increase our understanding of HL coordination chemistry with palladium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, aminobenzothiazole has gained significant attention due to its pharmacological activity, including anti-inflammatory, antifungal, anticonvulsant, analgesics, and anticancer activity. [4][5][6][7][8][9] It is reported that nitrogen-containing heterocyclic rings like aminobenzothiazole offer a polarized character, which plays a significant role in the stability of the molecule-receptor complex. It generally increases the complex stability by establishing an optimum interaction that produces anticancer effects.…”
mentioning
confidence: 99%